The effect of meningococcal vaccines on new generation of systemic inflammatory markers in children - Omer Okuyan; Neval Elgormus; Seyma Dumur; Ugurcan Sayili; Hafize Uzun (Exploration of Immunology)
Aim: Immunization with meningococcal vaccine (MV) is the most effective measure to control and prevent the transmission of meningococcal infections. In this study, in order to support the appropriate use of various MVs in the prevention of meningococcal meningitis (MM), the effects of MVs, especially single-dose and inter-booster administered, on inflammatory parameters in < 5-year-old children were investigated. Methods: A total of 464 healthy children were included in this study. The data of those who received the first 2 doses at 2-month intervals and the next dose between 8–12 months were included. Nimenrix® (Pfizer) administered as a single dose to children from 12 months of age. Bexsero® (GSK) was administered as 2 + 1 doses under 2 years of age and 2 doses 2 months apart over 2 years of age. Neutrophil, lymphocyte, monocyte, platelet counts, C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), derived NLR (dNLR), platelet-to-lymphocyte ratio (PLR), systemic inflammation response index (SIR-I), and systemic immune inflammation index (SII) were evaluated. Results: Of the 464 participants, 58.2% were male, with a mean age of 3.81 years, and both sex ratios and ages were similar across the Nimenrix and Bexsero groups. The laboratory and inflammatory parameters of the two vaccine groups were similar. In both vaccine groups, changes in laboratory parameters before and 3-months after vaccination were similar. The changes in laboratory parameters over time between vaccine groups and their interactions were not significant. Conclusions: The NLR, dNLR, PLR, SIR-I, and SII are useful biomarkers indicating the inflammatory response of Nimenrix and Bexsero vaccines. Inflammatory markers can be used as both a safety endpoint and a protection endpoint for MVs (Nimenrix and Bexsero). However, further studies involving larger patient cohorts as well as detailed laboratory data on specific markers of inflammation are needed to draw comprehensive conclusions regarding the inflammatory response following vaccination.